Optimizing the Health of Type 2 Diabetes Mellitus Patients with Islamic Approaches and Volunteers - Muhamad Faizun; Mohammad Fanani; Achmad Arman Subijanto; Sapja Anantanyu; Fiki Amalia; Agus Dwianto (Qubahan Academic Journal)
Depression, which is prevalent in patients with diabetes mellitus, can be addressed by integrating Islamic mindfulness practices and family volunteer support. This study assessed the impact of combining Islamic mindfulness practice (IMP) with family volunteer support on depressive symptoms and knowledge in patients with type 2 diabetes mellitus (T2DM). A total of 120 Muslim patients diagnosed with T2DM and having a Beck's Depression Inventory (BDI) score >17 participated. The intervention group engaged in facilitated group discussions led by family volunteers, focusing on Islamic mindfulness techniques and diabetes education. The results underscored the importance of family volunteer support combined with Islamic awareness for T2DM patients with depression, showing reduced depressive symptoms as measured by the BDI after the intervention. In addition, the intervention group showed improved knowledge of the chronic condition based on Diabetes Knowledge Questionnaire (DKQ) data compared to the control group. In conclusion, integrating Islamic awareness and family volunteer support in caring for T2DM patients with depression can reduce depressive symptoms and improve T2DM knowledge.